A persistence model of the national minimum wage - Melanie K. Jones; Richard J. Jones; Philip D. Murphy; Peter J. Sloane (Institute for the Study of Labor (IZA), 2007)
This paper utilises the panel element of the BHPS (waves 9 to 14) to examine the dynamics of the National Minimum Wage (NMW) introduced to Britain in 1999. Specifically a persistence measure based on a random effects probit model for those affected by the NMW is constructed. The conditional probabilities imply some degree of state dependence, but there is also a considerable amount of turnover from one year to the next among those affected by the NMW
urn:nbn:de:101:1-20080422258
Keywords: 330; Mindestlohn; Lohnrigidität; Soziale Mobilität; Schätzung; Großbritannien